ZnO nanostructures as sensing element of acoustic wave sensor - Bogdan, Oleksandr; Orlov, Anatolii; Petrischev, Oleg; Ulianova, Veronika (Eastern-European Journal of Enterprise Technologies, 2012)
In spite of the wide application of SAW devices the investigation of novel sensitive materials, their synthesis methods is continuously carried out. For further quality and accuracy enhancement, simplification of manufacturing and improvement of applying the simulation of novel acoustic wave sensors operation should be performed. In ZnO nanorods-based sensors propagating surface wave imparts following motion to the ends of hydrothermally grown between two interdigitated transducers rod nanostructures: vertical displacement, horizontal displacement and rotations in plane. Thus, response of nanostructured elements to that displacements and kinematic characteristics of Relay waves are evaluated. During the simulation the frequency equation from which we can determine the velocity of propagation of a surface wave for a given geometrical parameters of the rod nanostructures, the values of the density of their distribution on the surface of the half-space and added masses is obtained. This model simplifies the development and analysis of the results from ZnO nanorods-based SAW sensors for biological and chemical agents, including molecules, cells and tissues. Performed simulation extends the range of tools for further development of nanorods-based SAW sensors due to comprehensive math-based explanation of their operating principles